Implementação e sistematização de serviço de gerenciamento da terapia medicamentosa oferecido a pacientes com câncer de mama - Maria Angela Ribeiro (2017)
Objective: To systematize the processes of the clinical service in the oncology sector of a hospital of high complexity and implement the Medication Therapy Management (MTM) in the care of women with breast cancer. Method: It is a qualitative research using the action research methodology as proposed by Kurt Lewin, with emphasis on group dynamics, field theory, retention and conduction forces. It was used as a data collection technique: participant observation between August 2014 and December 2016, semi-structured interviews with pharmacists and pharmacy residents, field journal notes and document analysis. The initial study sample consisted of 21 pharmacists. As the study progressed, and the process of action and reflection associated with the methodology of action research progressed, several participants withdrew from the study. Of the initial total, four pharmacists, including the first author, and five residents completed the study. Results: The thesis is presented in the format of articles. The first article, whose objective was to implement and systematize a comprehensive medication management service, presents six major themes that emerged in four cycles of the action research process: 1. Resistance is human, the management of conflict is necessary; 2. Insecurity with being a clinician; 3. Management of change supported by driving forces; 4. Pharmaceutical care fostering professionals self-efficacy; 5. Documentation as the conducting wire of the practice; 6. The advantages of a systematized practice. The second article, whose objective was to present the experience of pharmacy residents with learning and building their clinical practice, describes three other themes: 1. A second pharmacy course; 2. Redesigning the pharmacy practice: from its philosophy to self-efficacy; 3. Training for SUS and for life: the role of Permanent Education. Conclusion: the study provided an understanding of the process of implementation of the clinical service from the perspective of the pharmacists involved. It also produced knowledge about the experiences of pharmacists while living the process of transforming their profesional practice to offer a systematized and patient-centered service. Lewin's structure supported the introduction of a new work path for pharmacists, which has the potential to be operationalized as an innovative technology for the Brazilian healthcare system: the MTM services.